Toxicity of Low-dose Graphene Oxide Nanoparticles in an in-vivo Wild Type of Caenorhabditis elegans Model - Ming-Hsien Tsai; How-Ran Chao; Jheng-Jie Jiang; Yu-Hsieh Su; Mariene-syne P. Cortez; Lemmuel L. Tayo; I-Cheng Lu; Hao Hsieh; Chih-Chung Lin; Sheng-Lun Lin; Wan Nurdiyana Wan Mansor; Ching-Kai Su; et al. (Aerosol and Air Quality Research)
Abstract Carbon-based engineered nanomaterials, such as graphene oxide nanoparticles (GO NPs), are widely available for application, but their potentially adverse health effects on humans still require investigation. In this study, the environmental levels of GO NPs are addressed to examine whether GO leads to adverse effects on an in-vivo model of Caenorhabditis elegans (C. elegans). Nematodes with prolonged exposure (L1 larvae to young adult) to GO NPs at 0.00100, 0.0100, 0.100, and 1.00 μg L−1 were used to evaluate the potential toxic effects, including lethality (acute toxicity), reproductive (brood size) and neurological (locomotion including head thrash and body bend) responses, longevity (lifespan), and oxidative stress (gene expression of sod-1, sod-3, and clt-2). Prolonged exposure to GO NPs was not found to induce lethality at the selective levels. In the brood-size and head-thrash tests, the biological responses in nematodes were significantly reduced at 0.0100-1.00 ng L−1 GO NP exposure as compared with the untreated control. The nematodes exposure to GO NPs at 0.00100–1.00 ng L−1 exhibited significant delays in body bending behavior compared with the control. In the examination of the longevity of nematodes, it was found that the lifespan of all GO NP-exposed worms was significantly shortened as compared to the untreated worms. Gene expression of sod-1, sod-3, and ctl-2 presented significantly higher induction folds in the exposed worms compared with the controls. Consequently, prolonged exposure to the low-dose GO NPs might be associated with disruption of reproduction and locomotion, attenuation of longevity, and induction of oxidative stress in nematodes.